(untitled) (Journal of Asian Development Studies, 2026)
The longjump is a complex athletic event influenced by technical skills, physical fitness, and anthropometric factors. Plyometric training (PT) has been shown to enhance neuromuscular performance, yet its effectiveness in female collegiate athletes remains underexplored. This study evaluated the effects of an 8-week plyometric training program on anthropometric characteristics, physical fitness, and long jump performance in female college students. Thirty female participants (mean age = 17.4 ± 2.6 years) were randomly allocated to an experimental group (EG; n=15) who performed plyometric training, and a control group (CG; n=15) who maintained standard physical education activities. Pre-and post-intervention assessments included anthropometry (height, weight, girths, lengths, breadths), physical fitness (vertical jump, standing broad jump, 30-m sprint, 600-m endurance run, sit-and-reach, agility T-test, hexagon test), and effective long jump distance. Data were analyzed using independent t-tests (p < 0.05). Comparedwith the CG, the EG demonstrated significant improvements in vertical jump (+30.2%, p<0.001), standing broad jump (+26.3%, p=0.01), flexibility (+18.8%, p<0.001), agility (T-test −26.2%, p=0.01; hexagon test −26.4%, p=0.01), and endurance (−35.9% completion time, p=0.02). Long jump performance improved markedly in the EG (pre: 2.24 ± 0.56 m vs. post: 4.12 ± 0.52 m; p<0.001). Anthropometric changes were minimal, with only body weight decreasing significantly in the EG (−8.3%, p=0.03). Kinematic analysis revealed minor technique modifications, with significant improvements observed only in right elbow angles at take-off and touchdown (p=0.01). Eight weeks of plyometric training significantly enhanced physical fitness and long jump performance in female collegiate athletes, with limited anthropometric changes. Plyometric training is an effective and time-efficient intervention to improve explosive power, agility, flexibility, and endurance in young female athletes.